TNF-α Orchestrates Experience-Dependent Plasticity of Excitatory and Inhibitory Synapses in the Anterior Piriform Cortex - Guo, Anni; Lau, Chunyue Geoffrey (Frontiers in Neuroscience, 2022)
Homeostatic synaptic plasticity, which induces compensatory modulation of synapses, plays a critical role in maintaining neuronal circuit function in response to changing activity patterns. Activity in the anterior piriform cortex (APC) is largely driven by ipsilateral neural activity from the olfactory bulb and is a suitable system for examining the effects of sensory experience on cortical circuits. Pro-inflammatory cytokine tumor necrosis factor-α (TNF-α) can modulate excitatory and inhibitory synapses, but its role in APC is unexplored. Here we examined the role of TNF-α in adjusting synapses in the mouse APC after experience deprivation via unilateral naris occlusion. Immunofluorescent staining revealed that activity deprivation increased excitatory, and decreased inhibitory, synaptic density in wild-type mice, consistent with homeostatic regulation. Quantitative RT-PCR showed that naris occlusion increased the expression of Tnf mRNA in APC. Critically, occlusion-induced plasticity of excitatory and inhibitory synapses was completely blocked in the Tnf knockout mouse. Together, these results show that TNF-α is an important orchestrator of experience-dependent plasticity in the APC.